Penatalaksanaan Multipel Fraktur Maksilofasial dengan Rekonstruksi Mandibula sebagai Tahap Awal Berdasarkan Prinsip Facial Buttress: Laporan Kasus - Iwan Setiawan Adji; Hanani Adeliya Hasyim; Rheinasya Adisty Almeyda Putri; Shinta Aulia Rahmadhanti; Faryn Dzaky Al A’la; Annisa Naura Azahra (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Multiple facial fractures are complex injuries commonly caused by high-energy trauma, particularly traffic accidents. These injuries may involve multiple facial skeletal structures, resulting in impaired mastication, occlusion, respiration, vision, and facial aesthetics. Appropriate management requires anatomical reconstruction based on the principles of open reduction and internal fixation (ORIF), with an appropriate fixation sequence to achieve optimal functional and cosmetic outcomes. Case Report: A 20-year-old male presented to the emergency department following a traffic accident, complaining of severe facial pain accompanied by bilateral epistaxis. Physical examination revealed edema, deformity, crepitus, and tenderness in the nasal, naso-orbito-ethmoid (NOE), zygomatic, bilateral maxillary, and mandibular regions. Laboratory examination revealed anemia due to acute blood loss, leukocytosis with neutrophilia, an increased neutrophil-to-lymphocyte ratio (NLR), and abnormalities in coagulation parameters. The patient was diagnosed with multiple facial fractures involving the nasal bone, NOE complex, left zygomatic bone, bilateral maxilla, and mandibular symphysis. ORIF was performed using a reconstruction sequence beginning with the mandible to restore occlusion, followed by reconstruction of the zygomaticomaxillary, nasomaxillary, and NOE buttresses using plates and screws. Discussion: Beginning reconstruction with the mandible provides a stable occlusal reference, thereby facilitating the repositioning of other facial structures. This approach is consistent with the principles of facial buttress reconstruction, which aim to restore bony continuity, masticatory function, facial stability, and aesthetic outcomes. Changes in laboratory parameters reflected the post-traumatic inflammatory response and the process of erythrocyte regeneration following blood loss. Conclusion: The management of multiple facial fractures requires comprehensive clinical evaluation, adequate supporting examinations, and reconstruction based on the principles of facial buttress restoration. ORIF performed with an appropriate fixation sequence can optimally restore facial function and anatomy while reducing the risk of long-term complications.